Implementation of Interdisciplinary Home Visit Services to Enhance the Quality of Life for Elderly with Dementia in Yogyakarta - Mei Rianita Elfrida Sinaga; Vivi Retno Intening; Joel Rey Acob (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Dementia is rapidly increasing in low- and middle-income settings. Elderly individuals with dementia often experience a decline in quality of life due to limitations in cognitive, physical, and social functions. Interdisciplinary Home Visits (IHV) promise support for elderly dementia patients and their families, but evidence and evaluations of their implementation in Yogyakarta, Indonesia, are still scarce. This study aims to implement and evaluate the effectiveness of IHV in improving the quality of life for elderly individuals with dementia in Yogyakarta.Method: A quasi-experimental approach with a pretest-posttest design without a control group was applied in this study. The IHV team consists of nurses, physical therapists, and informal caregivers. The purposive sampling technique was applied to 30 elderly individuals with dementia who were willing to participate in the series of research activities. The IHV program intervention was conducted over four weeks, with program assessment, implementation, and evaluation stages based on the needs of elderly individuals with dementia. Quality of life assessment was conducted using the Indonesian version of the WHOQoL-BREF questionnaire, which includes four domains: physical, psychological, social, and environmental. Data analysis was performed using the Wilcoxon test.Result: There was an improvement in all domains of quality of life for the elderly, with Z (p) results of physical -4.798 (p<0.001), psychological -4.804 (p<0.001), social -4.736 (p<0.001), environmental -4.437 (p<0.001), and r values of 0.876, 0.877, 0.865, and 0.810.Conclusion: Interdisciplinary Home Visit (IHV) has a significant impact on improving the quality of life for elderly individuals with dementia across all physical, psychological, social, and environmental domains. These findings support scaling up and conducting controlled trials to ensure effectiveness and sustainability in primary care in Indonesia.